PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS DI KOTA PADANG - Fatmawanti, Besse; Gantika, Naldi (UNES Law Review, 2019)
Research is important written in a journal is caused by several reasons: First , fulfillment of public services, especially for persons with disabilities, is an obligation and responsibility of the government in terms of fulfillment, both in the form of public services in the form of roads and sidewalks that are useful for the movement of persons with disabilities or for their mobility from one place to another, as well as supporting life supporters of disability. Article 2 of Law No. 39 of 1999 concerning Human Rights states that the Republic of Indonesia recognizes and upholds human rights and basic human freedoms as rights which naturally inherit to and are inseparable from humans, which must be protected, respected and enforced for the sake of increasing human dignity . Then it is also regulated that the right to protect, respect and uphold human rights is the government and in full in Article 71 of Law No. 39 of 1999 concerning Human Rights stated that "the Government is obliged and responsible to respect, protect, enforce and promote human rights regulated in this law, other laws and regulations, and international law on human rights received by the Republic of Indonesia. And it should not be forgotten also Article 72 which reads that the obligations and responsibilities of the government as referred to in Article 71 include effective implementation steps in the legal, political, economic, social, cultural, defense and security fields of the state and other fields. At least, there are 10 types of rights regulated in Law No. 39 of 1999 concerning Human Rights, a) the right to life, b) the right to family and continuing descent, c) the right to self-development, d) the right to justice, e) the right to personal freedom, f) the right to security, g) the right to welfare, h) the right to welfare, i) the right to participate in government, j) the right of women, k) the rights of the child.